A Randomized, Controlled Comparison of 180 Versus 360 Degrees Selective Laser Trabeculoplasty in Open Angle Glaucoma and Glaucoma Suspects. Issue 4 (8th April 2023) - Michaelov, Evan; Sachdeva, Robin; Raniga, Aparna; Lin, Tony
Abstract : Précis: Three hundred sixty degrees selective laser trabeculoplasty (SLT) produces greater intraocular pressure (IOP) lowering effects with no changes in safety profile compared with 180 degrees SLT. Purpose: To determine whether there is any difference in the IOP lowering effects and safety profiles of 180 versus 360 degrees SLT, using a paired-eye design to limit confounders. Methods: This single-center randomized control trial included patients presenting with treatment naïve open angle glaucoma or glaucoma suspects. Once enrolled, 1 eye was randomized to 180 degrees SLT, and the other was treated with 360 degrees SLT. Patients were followed for 1 year and assessed for change in visual acuity, Goldmann IOP, Humphrey visual fields, retinal nerve fiber layer thickness, optical coherence tomography derived cup to disc ratio, and any adverse events or requirements for additional medical interventions. Results: A total of 40 patients (80 eyes) were included in the study. IOP in the 180 degrees group was reduced from 25.3±2.3 mm Hg to 21.5±2.7 mm Hg, and in the 360 degrees group, from 25.5±2.1 mm Hg to 19.9±2.6 mm Hg ( P <0.01), both at 1 year. There was no significant difference in the number of adverse events or serious adverse events in the 2 groups. There were no statistically significant differences in visual acuity, Humphrey visual field mean deviation, retinal nerve fiber layer thickness, or C:D ratio at 1-year follow-up. Conclusion: At 1 year, 360 degrees SLT was more efficacious at lowering IOP compared with 180 degrees SLT with a similar safety profile in patients with open angle glaucoma and glaucoma suspects. Further studies are needed to determine the long-term effects.